Bibliometric: The Role of Science Learning on Student Motivation in Moral Education - Widyaningsih, Mia; Robandi, Babang; Mudzakir, Ahmad (Universal Education Jurnal Teaching and Learning, 2025)
The purpose of this research was to find out the development and understanding of the role of science learning on students' motivation in moral education using a bibliometric study on the Google Scholar database with the help of VOS viewer. From 2019 to 2023, 953 articles were found from Google Scholar, and 795 were selected, which were related to content, based on data collection results using the keywords "science learning", "student motivation", and "moral education". The results of data searches for the last five years show that from 2019 to 2023, the number of publications has decreased. Three types of visualizations in the data mapping analysis were added: network visualization, overlay visualization, and density visualization, to support the analysis of related articles. It is hoped that the results of this study will help researchers identify developments and understanding of international research related to the keywords proposed.